2016
DOI: 10.1111/ctr.12807
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic abscess: a rare complication after liver transplant

Abstract: Hepatic abscess after liver transplantation may be treated successfully with percutaneous and endoscopic intervention, along with antibiotics according to the results of microbial cultures of blood and/or abscess aspirates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 24 publications
8
35
0
1
Order By: Relevance
“…When comparing our data to other published series of PLA-LTR, we observed a longer time from liver transplantation to PLA diagnosis than previously reported. [16][17][18][19][20][21][22] Of note, Justo et al, in a recent Spanish series, also observed a long median interval of 39.7 months from liver transplantation, which contrasted with the shorter duration (2-13 months) reported previously by most authors. [16][17][18][19]22 The majority of PLA-LTR were caused by ischemic cholangitis due to hepatic arterial thrombosis (HAT-IC), which occurred later in our case series (8/10 late HAT) than in most of the others.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…When comparing our data to other published series of PLA-LTR, we observed a longer time from liver transplantation to PLA diagnosis than previously reported. [16][17][18][19][20][21][22] Of note, Justo et al, in a recent Spanish series, also observed a long median interval of 39.7 months from liver transplantation, which contrasted with the shorter duration (2-13 months) reported previously by most authors. [16][17][18][19]22 The majority of PLA-LTR were caused by ischemic cholangitis due to hepatic arterial thrombosis (HAT-IC), which occurred later in our case series (8/10 late HAT) than in most of the others.…”
Section: Discussionmentioning
confidence: 96%
“…[16][17][18][19][20][21][22] Of note, Justo et al, in a recent Spanish series, also observed a long median interval of 39.7 months from liver transplantation, which contrasted with the shorter duration (2-13 months) reported previously by most authors. [16][17][18][19]22 The majority of PLA-LTR were caused by ischemic cholangitis due to hepatic arterial thrombosis (HAT-IC), which occurred later in our case series (8/10 late HAT) than in most of the others. [16][17][18][19]22 Early HAT (within 30 days after liver transplantation) is more frequently related to technical problems (complex hepatic artery anatomy, hepatic artery dissection, atheroma, etc).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although bacteria represent the most common causative agents, fungi cannot be neglected in the differential diagnosis, considering their impact, in terms of morbidity and mortality, in the setting of posttransplantation infections. 81 Indeed, in the light of the recommendations from the most authoritative international societies, antifungal prophylaxis following OLT, to prevent IFIs, is not mandatory for low-risk patients, but it is necessary under several circumstances: 1) only against Candida spp. for patients with perioperative Candida colonization complicated operations or choledochojejunostomy anastomosis and 2) against both Candida and Aspergillus for patients at high risk, undergoing renal replacement therapy posttransplant and with the high probability of reoperation.…”
Section: Discussionmentioning
confidence: 99%